2020
DOI: 10.1002/ccd.28886
|View full text |Cite
|
Sign up to set email alerts
|

Three contemporary thin‐strut drug‐eluting stents implanted in severely calcified coronary lesions of participants in a randomized all‐comers trial

Abstract: Objective The objective was to assess the 2‐year clinical performance of three drug‐eluting stents in all‐comer patients with severely calcified coronary lesions. Background Severe lesion calcification increases cardiovascular event risk after coronary stenting, but there is a lack of data on the clinical outcome of all‐comers with severely calcified lesions who were treated with more recently introduced drug‐eluting stents. Methods The BIO‐RESORT trial (http://clinicaltrials.gov: NCT01674803) randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(44 reference statements)
0
7
1
Order By: Relevance
“…Interestingly, while there was a trend for less TVR associated with BP-EES in several studies 2 , 13 , 28 , 29 , this meta-analysis of all available RCTs showed no significant difference between BP-EES and contemporary DP-DES. The outcomes, while demonstrating no superiority of BP-EES, suggest that the BP-EES is not inferior to newer, widespread used DP-DES.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, while there was a trend for less TVR associated with BP-EES in several studies 2 , 13 , 28 , 29 , this meta-analysis of all available RCTs showed no significant difference between BP-EES and contemporary DP-DES. The outcomes, while demonstrating no superiority of BP-EES, suggest that the BP-EES is not inferior to newer, widespread used DP-DES.…”
Section: Discussionmentioning
confidence: 53%
“…1). Fifteen RCTs met our inclusion criteria 2,13,[25][26][27][28][29][30][31][32][33][34][35][36][37] . Some data are from shorter follow-up time of the same study 25,31 or from a single center in a multi-center study 13,[36][37][38] .…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…There is accumulating evidence that newer ultrathin stents and biodegradable polymers are associated with more favorable results in patients undergoing PCI compared to thicker strut SGDES and durable polymers. In post hoc analyses of the BIO-RESORT trial, Synergy EES (strut thickness 74 μm) were associated with lower rates of TLR compared to Resolute Integrity ZES (strut thickness 91 μm) in small coronary arteries [ 13 ] and calcified lesions [ 14 ]. In the BIOFLOW V [ 15 ] and BIOSTEMI [ 16 ] trials, superior outcomes were observed with Orsiro CoCr-SES-BP (strut thickness 60/80 μm) compared to Xience CoCr-EES-DP.…”
Section: Discussionmentioning
confidence: 99%
“…Second generation DES (SGDES) have been a further improvement on the first-generation stents in terms of safety and efficacy when used after RA [ 10 , 11 , 12 ]. Additionally, there is accumulating evidence that newer ultrathin stents and biodegradable polymers are associated with more favorable results in patients undergoing PCI compared to thicker strut SGDES and durable polymers [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 However, although 17.3% lesions in this registry were total occlusions, no signal even remotely suggestive of a clinically relevant problem due to insufficient radial force was observed. Neither has such a problem been reported in the BIORESORT (Comparison of BIOdegradable Polymer and DuRablE Polymer Drug-eluting Stents in an All COmeRs PopulaTion) small coronary vessel subgroup 4 or calcified coronary lesion subgroup, 5 which reported implantation of ultrathin strut stents. Limitations include retrospective, single-arm, and observational study design and the lack of head-to-head comparison with other latest generation stents.…”
mentioning
confidence: 99%